Amelioration in nanobiosensors for the control of plant diseases: current status and future challenges - Virk, Verinder; Deepak, Himani; Taneja, Khushbu; Srivastava, Rishita; Giri, Sadhana (Frontiers in Nanotechnology, 2024)
Increase in global population has a tremendous impact on sustainable agri-food practices. With the growing world population, various modern technologies are being utilized more often resulting into the opening of tremendous opportunities in agriculture and food sectors. Nanotechnology in used in agri-food sectors for a variety of purposes, including encapsulating flavour, pest/pathogen diagnosis, production, processing, storage packaging and transportation of agricultural products. Plant pathogenic microorganisms including bacteria, viruses, fungi and nematodes significantly impose impact on global economy. Particularly, the advancement in nanotechnology including nanobiosensors have been used in the detection of plant diseases, detection of pathogens, evaluation and examination of infections caused by microorganisms, management of diseases and thus promoting food security. Apart from management of plant diseases, nanobiosensors offers better opportunities in sustainable agri-food productions by controlling physical, chemical and biological processes thus increasing food safety and improving agriculture economy as well. The present review outlines the amelioration in nano integrated nanobiosensors for better agricultural and food practices.